बौद्ध धर्म के उत्थान और विस्तार में थेरवाद और महायान सम्प्रदाय की भूमिका ! (Bodhi Path, 2023)
India's gastronomy is extremely diverse. Its interior is even more colorful and beautiful. Here, the rise of humanity and civilization occurred. The birthplace of many religions and philosophies. From the holy lake of Manasarovar sprung various streams of thought that not only influenced India, but also many countries worldwide, and continue to influence them today in one way or another. India, with its multitude of pilgrimage sites, is the birthplace of various religions like Buddhism, Jainism, Hinduism, and Sikhism.